Factors influencing behavioural intention to use mobile banking among retail banking clients - De Leon, Myra V (Faculty of Communications Science, Dr. Soetomo University, 2019)
Mobile banking enables clients to bank virtually without restrictions to time and place. Despite wide adoption of mobile banking around the world, use of mobile banking is still considered low. Philippines has the lowest digital banking penetration across Asian countries although the country known for the title of â€œSMS-intensive country in the worldâ€. Factor analysis, partial least squares structural equation modelling (PLS-SEM) and ANOVA with bootstrapping were used to test research hypotheses. Findings from 212 Universal bank retail branch clients show that perceived ease of use, perceived usefulness, social influence and trust propensity have significant positive influence on behavioral intention to use mobile banking. Results also show that respondents with matured age (22 years and above), male, at least Bachelor Degree graduate and receiving a monthly income higher than Php 10,001 has higher behavioral intention. This study is relevant for proposing marketing strategies to increase adoption of mobile banking and contribute for further advancement on technology acceptance literature.